Listening in to a conversation enhances theory of mind - Emanuele Castano; Alison Jane Martingano; Gabriana Basile; Elly Bergen; Evelyn Hye Kyung Jeong (Current Research in Ecological and Social Psychology, 2023)
Activities that require mentalizing, such as meditating or reading literary fiction, have been shown to enhance Theory of Mind (ToM) (e.g., Tan, Lo, and Macrae, 2014; Kidd & Castano, 2013). In this article, we conjecture that relatively greater mentalizing effort also occurs when individuals can only listen in on a conversation, compared to those who actively participate in it. Therefore, those who listen in should show better performance on subsequent ToM tasks. Participants (N = 77) were divided into triads and randomly assigned to be Interlocutors (a Director and a Matcher) or Listeners. In each triad, Interlocutors completed a collaborative figure matching task while talking to each other, while Listeners completed the same task while listening to live audio of the Interlocutors' conversation. All participants then completed two Theory of Mind measures. Multivariate analyses show that Listeners outperformed Interlocutors on both measures, but the pattern is significant only for one measure. These results complement existing theorizing and findings regarding the potential benefit of participating in activities that train ToM and may also help explain the often-observed stronger ToM performance of those (e.g., women) who, at least in certain contexts, have typically been discouraged from participating actively in conversations.